Risk factors for the occurrence of ampullary tumors: A case‐control study. Issue 7 (27th July 2022) - Zaccari, Piera; Archibugi, Livia; Belfiori, Giulio; Nista, Enrico; dell'Anna, Giuseppe; Crippa, Stefano; Schepis, Tommaso; Tacelli, Matteo; Aleotti, Francesca; Petrone, Maria Chiara; Mariani, Alberto; Costamagna, Guido; et al.
Abstract: Background: The incidence of ampullary tumors is increasing but data on association with an increased exposure to certain risk factors are scanty. Objective: To investigate risk and protective factors associated with the occurrence of ampullary tumors and whether these factors differ between ampullary tumors of the intestinal and pancreatobiliary subtypes or between adenomas and carcinomas. Methods: The association between a large set of exposome features and ampullary tumors occurrence was investigated in a bi‐centric case‐control study after ethic committee approval and power calculation. Results: In 223 histologically confirmed patients and 446 controls, previous cholecystectomy (odd ratio [OR] = 2.07; 95% confidence interval [CI] = 1.34–3.20) and proton pump inhibitors use (OR = 1.66; 95% CI = 1.16–2.37) were associated with increased risk of ampullary tumors, aspirin use (OR = 0.57; 95% CI = 0.36–0.90) and light alcohol intake (OR = 0.54; 95% CI = 0.38–0.76) with reduced risk. A previous cholecystectomy was also associated with tumors of intestinal subtype and with both adenomas and carcinomas, and proton pump inhibitors use with adenomas only. Smoking, body mass index, family history of cancers, previous ulcer, diabetes and use of statins, insulin and metformin were not significant factors. Conclusion: This is the first case‐control study specifically highlighting factors associated with the occurrence of ampullary tumors. We report factors that are novel and plausible, in keeping with mechanisms described for other gastrointestinal tumors and with potential clinical relevance.